2022
DOI: 10.1093/tas/txac133
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the vaginal microbiota of high and low producing Poll Merino and White Suffolk ewes

Abstract: There is a substantial, and growing, body of research focussed on manipulating gastrointestinal microbes to affect health and production. However, the maternal vaginal microbiota and its effects on neonatal inoculation and lifetime production have received little attention. We aimed to characterise the vaginal microbes of domesticated sheep to determine if they differ across sheep breeds with differing meat and wool growth potentials and to determine a link between vaginal microbes and high and low producing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…A member of the Fusobacteriota phylum, unclassified Leptotrichiaceae , was present in higher abundance during the beginning of gestation than in later weeks . Leptotrichiaceae was considered as normal vaginal microbiota of both Suffolk and Merino ewes during maintenance ( Greenwood et al, 2022 ) as well as in Rambouillet ewes ( Swartz et al, 2014 ). Conversely, Leptotrichiaceae was found in greater relative abundance in the vagina of ewes that were not successfully mated when compared to ewes that became pregnant ( Koester et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A member of the Fusobacteriota phylum, unclassified Leptotrichiaceae , was present in higher abundance during the beginning of gestation than in later weeks . Leptotrichiaceae was considered as normal vaginal microbiota of both Suffolk and Merino ewes during maintenance ( Greenwood et al, 2022 ) as well as in Rambouillet ewes ( Swartz et al, 2014 ). Conversely, Leptotrichiaceae was found in greater relative abundance in the vagina of ewes that were not successfully mated when compared to ewes that became pregnant ( Koester et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the sponges also worked to homogenize the populations of bacteria present regardless of the point in the ewe’s estrous cycle when the sponge was inserted ( Manes et al, 2010 ; Gatti et al, 2011 ; Martinez-Ros et al, 2018 ; Quereda et al, 2020 ). Other studies evaluated the vaginal microbiota of sheep using an alternate method – 16S rRNA gene sequencing ( Swartz et al, 2014 ; Serrano et al, 2020 ; Koester et al, 2021 ; Greenwood et al, 2022 ; Reinoso-Peláez et al, 2023 ). One of those studies ( Koester et al, 2021 ) was conducted in our laboratory and was based on three sampling time points.…”
Section: Introductionmentioning
confidence: 99%
“…Since Ma has the ability to colonize the mammary gland and the vagina [ 9 ] and LAB and Staphylococcus spp. seem to be part of the microbiota of these anatomical sites [ 18 , 19 , 20 , 25 , 50 ], the present study describes the in vitro interactions between Ma and wild strains of CNS and Enterococcus spp. isolated from raw milk and vagina, respectively, of clinically healthy small ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported Firmicutes as the most abundant phylum in ewes ( Serrano et al, 2020 ; Koester et al, 2021 ; Greenwood et al, 2022 ; Reinoso-Peláez et al, 2023 ) and cattle ( Laguardia-Nascimento et al, 2015 ; Bicalho et al, 2017 ; Giannattasio-Ferraz et al, 2019 ; Miranda-CasoLuengo et al, 2019 ; Chen et al, 2020 ; Quadros et al, 2020 ). The results of our study are consistent with these previous studies as Firmicutes was always the predominant phylum except in Tpreg_NP.…”
Section: Discussionmentioning
confidence: 99%
“…Ureaplasma spp. has also been shown to be common in the vaginal microbiota of domestic ruminants ( Swartz et al, 2014 ; Deng et al, 2019 ; Chen et al, 2020 ; Quadros et al, 2020 ; Serrano et al, 2020 ; Quereda et al, 2020a ; Koester et al, 2021 ; Greenwood et al, 2022 ). Additionally, Mycoplasmatales are sensitive to drops in the pH of the medium (below 7.4) ( Howard and Gourlay, 1978 ; Gómez-Martín et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%